Riboflavin-responsive lipid-storage myopathy caused by ETFDH gene mutations. Issue 2 (15th September 2009) - Wen, Bing; Dai, Tingjun; Li, Wei; Zhao, Yuying; Liu, Shuping; Zhang, Chunhua; Li, Honghao; Wu, Jinling; Li, Danian; Yan, Chuanzhu
Abstract : Background: Lipid-storage myopathy (LSM), defined by triglyceride accumulation in muscle fibres, is a heterogeneous group of lipid metabolic disorders predominantly affecting skeletal muscle. In the past 15 years, more than 200 cases of LSM have been reported in the Chinese literature, but the accurate pathogenic mechanisms are still unknown. Objective: In order to gain more insight into the metabolic and genetic dysfunctions of LSM, the authors described a group of Chinese patients with LSM who were very responsive to isolated riboflavin treatment (riboflavin responsive LSM, RR-LSM). Methods: Nineteen consecutive LSM patients collected during 1995–2007 in our Neuromuscular Laboratory who were dramatically responsive to riboflavin and presented with proximal muscle weakness, exercise intolerance and elevated serum CK but without episodic encephalopathy were subjected to pathological, biochemical and molecular analysis. Results: On the basis of muscle pathology, all 19 patients were diagnosed as LSM. Seventeen patients were suspected of having multiple acyl-coenzyme A dehydrogenase deficiency (MADD) according to blood acylcarnitine profiles and urine organic acid analysis. Genetic analysis identified 19 novel mutations in ETFDH gene in 18 patients, among which one was homozygote, 16 were compound heterozygotes, and one was a single heterozygote. No pathogenic mutation was detected in ETFA or ETFB genes. Western blot analysis showed there was no significant decrease in ETF:QO expression except for one patient. Conclusions: The research findings suggest that the majority of Chinese patients with RR-LSM are caused by a mild type of MADD with unique myopathy which is due to ETFDH gene mutation.